2019
DOI: 10.1111/ped.13921
|View full text |Cite
|
Sign up to set email alerts
|

Mesangial C4d deposition at diagnosis in childhood immunoglobulin A nephropathy

Abstract: Background Immunoglobulin A nephropathy (IgAN) is a major cause of end‐stage renal disease. Complement activation via the lectin pathway influences outcomes in IgAN. We examined the association of glomerular C4d deposition with clinicopathological severity at diagnosis and the disappearance of proteinuria in Japanese pediatric IgAN patients. Methods We retrospectively analyzed 25 children newly diagnosed with IgAN at Hokkaido University Hospital. We evaluated glomerular C4d immunofluorescent staining at diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 32 publications
0
13
0
3
Order By: Relevance
“…The possible underlying mechanism is that the risk of infection is increased in patients with MBL deficiency, and infection may induce impaired mucosal immune regulation, which promotes the progression of IgAN (136). The findings of many studies have suggested that the activated fragments of C4 deposited in the glomerular mesangium of patients with IgAN are more likely to be produced by the MBL pathway (137,138). Mesangial deposition of C4d has been identified as a significant risk factor for worsening renal function (139)(140)(141).…”
Section: Role Of Complements In Igan Pathogenesismentioning
confidence: 99%
“…The possible underlying mechanism is that the risk of infection is increased in patients with MBL deficiency, and infection may induce impaired mucosal immune regulation, which promotes the progression of IgAN (136). The findings of many studies have suggested that the activated fragments of C4 deposited in the glomerular mesangium of patients with IgAN are more likely to be produced by the MBL pathway (137,138). Mesangial deposition of C4d has been identified as a significant risk factor for worsening renal function (139)(140)(141).…”
Section: Role Of Complements In Igan Pathogenesismentioning
confidence: 99%
“…A total of 12 studies 8 , 9 , 10 , 11 , 12 , 13 , 14 , 16 , 20 , 21 , 22 , 23 with 1,251 patients were included. Reasons for exclusion are listed in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The studies involved 7 cohort and 5 cross-sectional studies. Nine studies 9 , 10 , 11 , 12 , 13 , 14 , 16 , 21 , 22 described the definition of glomerular C4d deposition, but the definition was inconsistent: “C4d positive” was defined as C4d deposition in >25% of nonsclerotic glomeruli in 3 studies, 12 , 14 , 21 >50% in 4 studies, 10 , 11 , 16 , 22 >75% in 1 study, 13 or greater than any 1 of nonsclerotic glomeruli in another study. 9 Four studies 10 , 11 , 21 , 23 (n = 484) recruited patients from Asian populations, including Japanese and Korean patients, and 8 studies 8 , 9 , 12 , 13 , 14 , 16 , 20 , 22 (n = 767) mainly recruited from European and South American populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations